A Comprehensive Evaluation of Hepatitis B Awareness, Knowledge Gaps, Health‐Seeking Behaviour, Risk Perceptions, and Vaccination Status Among University Students in Bangladesh: A Cross‐Sectional Study - Ali Ashraf Sakil; Md. Murad Hossain; Rayhan Ivan Rimon; Hasibur Rahaman; Rafaz Samnan Nahid; Md. Shohel Rana (Health Science Reports, 2026)
ABSTRACT Background Hepatitis B virus (HBV) infection is a significant public health problem globally. In Bangladesh, viral hepatitis is the most common liver disease, with approximately 10 million people infected with HBV. Methods The study was a cross‐sectional survey in which 440 respondents were randomly selected using Cochran's formula. The duration of the study was about 6 month (24th August 2024 to 28th February 2025). Data was gathered using a predesigned and structured questionnaire, which was distributed among the students. The collected data were then analysed utilizing Microsoft Excel 2016 and Stata 17 software for statistical processing and interpretation. Results Overall, the study found that respondents had a high level of awareness of hepatitis B, with most participants recognizing the disease and its major transmission routes and health consequences. Vaccine‐related knowledge was moderate, whereas hepatitis B vaccination uptake remained relatively low among the respondents and their family members. The mean (±SD) awareness, vaccine knowledge, and perception scores were 37.18 ± 11.16, 25.00 ± 10.88, and 22.38 ± 4.71 (each measured on a 50‐point scale), respectively. Multivariable logistic regression analysis showed that male participants were more likely to be vaccinated against hepatitis B than female participants (aOR = 1.74, 95% CI: 1.14–2.67). Participants with low awareness also had higher odds of being vaccinated than those with high awareness (aOR = 2.17, 95% CI: 1.09–4.36), while no significant association was observed for moderate awareness. Conclusion Less than half of the respondents had received the hepatitis B vaccine, with the most common reason for non‐vaccination being a lack of awareness of their vaccination status. Slightly over half of the respondents demonstrated satisfactory knowledge, attitudes, and practices regarding hepatitis B. These findings underscore the need for targeted education on hepatitis B infection, its risk factors, and the importance of vaccination among students in Bangladesh.